Morphological differentiation of seven species of the genus Heterocypris Claus, 1892 (Ostracoda, Crustacea) based on the upper lip - Karan-Žnidaršič, Tamara; Petrov, Brigita (Zootaxa, 2014)
Morphological differences of upper lip shape were analyzed in seven Heterocypris species occurring in the Mediterranean region. Descriptive observations and morphometric analysis of upper lip length, height and maximum height position are given for 17 populations from the Pannonian Plain, Balkan Peninsula and Iberian Peninsula. We found high variation in relative upper lip measurements between the species, indicating that upper lip traits can be used as additional taxonomic characters. The most distinctive upper lip shapes were noted in H. exigua and H. gevgelica, while the greatest intraspecific variability was present in H. barbara, H. incongruens and H. rotundata. Previously described qualitative characters in the form of differently arranged patches of pseudochaetae on the upper lip surface were also observed.